From Cellular to Metabolic: Advances in Imaging of Inherited Retinal Diseases - Deepika C. Parameswarappa; Ashwini Kulkarni; Niroj Kumar Sahoo; Srikanta Kumar Padhy; Sumit Randhir Singh; Elise Héon; Jay Chhablani (Diagnostics)
Background: Inherited retinal diseases (IRDs) are a genetically complex group of disorders, usually resulting in progressive vision loss due to retinal degeneration. Traditional imaging methods help in structural assessments, but limitations exist in early functional cellular-level detection that are crucial for guiding new therapies. Methods: This review includes a systematic search of PubMed and Google Scholar for studies on advanced imaging techniques for IRDs. Results: Key modalities covered are adaptive optics, fluorescence lifetime imaging ophthalmoscopy, polarization-sensitive optical coherence tomography, optoretinography, mitochondrial imaging, flavoprotein fluorescence imaging, and retinal oximetry. Each imaging method covers its principles, acquisition techniques, data from healthy eyes, applications in IRDs with specific examples, and current challenges and future directions. Conclusions: Emerging technologies, including adaptive optics and metabolic imaging, offer promising potential for cellular-level imaging and functional correlation in IRDs, allowing for earlier intervention and improved therapeutic targeting. Their integration into clinical practice may significantly improve IRD management and patient outcomes.